Mechanisms of immune response and cell death in ischemic stroke and their regulation by natural compounds - Gong, Zhaoyuan; Guo, Jing; Liu, Bin; Guo, Yang; Cheng, Cuicui; Jiang, Yin; Liang, Ning; Hu, Mingzhi; Song, Tian; Yang, Lu; Li, Huizhen; Zhang, Haili; et al. (Frontiers in Immunology, 2024)
Ischemic stroke (IS), which is the third foremost cause of disability and death worldwide, has inflammation and cell death as its main pathological features. IS can lead to neuronal cell death and release factors such as damage-related molecular patterns, stimulating the immune system to release inflammatory mediators, thereby resulting in inflammation and exacerbating brain damage. Currently, there are a limited number of treatment methods for IS, which is a fact necessitating the discovery of new treatment targets. For this review, current research on inflammation and cell death in ischemic stroke was summarized. The complex roles and pathways of the principal immune cells (microglia, astrocyte, neutrophils, T lymphocytes, and monocytes/macrophage) in the immune system after IS in inflammation are discussed. The mechanisms of immune cell interactions and the cytokines involved in these interactions are summarized. Moreover, the cell death mechanisms (pyroptosis, apoptosis, necroptosis, PANoptosis, and ferroptosis) and pathways after IS are explored. Finally, a summary is provided of the mechanism of action of natural pharmacological active ingredients in the treatment of IS. Despite significant recent progress in research on IS, there remain many challenges that need to be overcome.